Increased Circulating Chemerin in Relation to Chronic Microvascular Complications in Patients with Type 2 Diabetes. (16th July 2019) - Gu, Ping; Wang, Wei; Yao, Yue; Xu, Yixin; Wang, Liping; Zang, Pu; Ma, Jian; Yang, Cuihua; Liang, Junya; Lu, Bin; Shao, Jiaqing
Abstract : Objective . Type 2 diabetes (T2DM) is a global epidemic and increases mortality due to its vascular complications. Chemerin has been found to exert a major role in glucose and lipid metabolism. The aim of this study was to explore the correlation between plasma chemerin levels and microangiopathy in patients with T2DM. Methods . A total of 598 T2DM patients were classified into two groups: with and without microvascular complications. Anthropometric parameters and blood pressure were taken. The amounts of glycosylated hemoglobin, glucose, lipid profiles, creatinine, and chemerin concentrations in the blood were determined. The presence and severity of nephropathy, retinopathy, and neuropathy were also evaluated by specific tests. Results . Plasma levels of chemerin in diabetic subjects with microvascular complications were markedly elevated compared to those without. The number of microvascular complications increased with high plasma chemerin levels. Patients with high chemerin levels had an increased incidence of nephropathy and retinopathy. Furthermore, the chemerin plasma concentrations increased with the progression of diabetic nephropathy with highest values in macroalbuminuria groups. In contrast, no significant difference was observed in plasma chemerin levels between subjects with and without peripheral neuropathy. Pearson correlation analysis showed that plasma chemerin levels were positively related to duration of diabetes, serum creatinine, and 24-hour urine albumin excretion, even after multiple adjustments. Using logistic regression analysis, plasma chemerin concentrations were independently associated with the presence of nephropathy and retinopathy, not neuropathy. Conclusion . This study elucidated a positive correlation between increased chemerin levels and the development of some subtypes of diabetic microangiopathy.